Applications of 445nm soft tissue diode laser in soft tissue dental surgeries: A case series - Ul Haque, Aehad; Lal, Nand; Rastogi, Pavitra; Kaushal, Shalini; Verma, Manisha (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: Through the recent years various types of lasers have found use in dentistry. Among them diode lasers have gained a special place in the arena of soft tissue surgery. Purpose: To substantiate the applicability of low wavelength Diode Laser in soft tissue dental surgeries. Cases: Five different cases in which soft tissue dental surgery was indicated, were included: (1) A 21-year-old female patient who underwent frenectomy; (2) A 24-year-old female patient who underwent excision of gingival polyp; (3) A 30-year-old patient who underwent Gingivectomy; (4) A 32-year-old female patient who underwent surgical crown lengthening and (5) A 28-year-old male patient who underwent operculectomy. Case Management: Each of these patients was successfully treated using low wavelength 445nm Soft Tissue Diode Laser. Conclusion: All the patients experienced normal post-operative healing without any complications. The overall outcome in each case was favourable. The use of low wavelength diode lasers is strongly suggested for soft tissue dental surgeries, owing to their ease of use, versatility, minimal thermal damage and good post-operative healing.